2022
DOI: 10.3389/fonc.2022.884854
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Diffusion Kurtosis Imaging and Intravoxel Incoherent Motion Diffusion-Weighted Imaging Parameters in Preoperative Evaluation of Pathological Grades and Microvascular Invasion in Hepatocellular Carcinoma

Abstract: BackgroundCurrently, there are disputes about the parameters of diffusion kurtosis imaging (DKI), intravoxel incoherent motion (IVIM), and diffusion-weighted imaging (DWI) in predicting pathological grades and microvascular invasion (MVI) in hepatocellular carcinoma (HCC). The aim of our study was to investigate and compare the predictive power of DKI and IVIM-DWI parameters for preoperative evaluation of pathological grades and MVI in HCC.MethodsPubMed, Web of Science, and Embase databases were searched for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…survival in patients with HCC has remarkably improved owing to the recent advances in imaging diagnosis, surgical techniques, targeted therapies, and immunotherapy [20][21][22][23][24]. Despite these advancements, patients diagnosed with HCC and MVI for the rst time present with low 5-year survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…survival in patients with HCC has remarkably improved owing to the recent advances in imaging diagnosis, surgical techniques, targeted therapies, and immunotherapy [20][21][22][23][24]. Despite these advancements, patients diagnosed with HCC and MVI for the rst time present with low 5-year survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was found that only IVIM-derived D t showed statistical significance, while D p and f exhibited high variance and did not demonstrate statistical differences, consistent with our findings. 22 , 23 , 26 , 27 The liver exhibits distinctive histological features, encompassing various types of vessels such as arteries/arterioles, portal veins/venules, and hepatic veins/venules. In addition, it contains sinusoid capillaries, bile ducts, and an extensive lymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous publications that have identified significantly lower diffusion coefficients as indicators of MVI-positive HCC. [22][23][24] 2) D f , on the other hand, reflects perfusion-related diffusion. While exuberant neovascularization is essential to meet the demands of oxygen and nutrient supply during hepatocarcinogenesis, these neovascular vessels are often characterized by vascular leakage and defective vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the correlation between imaging signs and histological classification can help clinicians choose appropriate preoperative treatment strategies. The postoperative survival rate of patients with well- and moderately differentiated HCC is significantly higher than that of patients with poorly differentiated HCC, and the 5-year postoperative recurrence rate of poorly differentiated HCC is as high as 70% [ 21 ]. For MVI-positive patients, the surgical resection area or radiofrequency ablation area must be expanded and systemic adjuvant therapy must be performed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%